Association study between hypothalamic functional connectivity, early nutrition, and glucose levels in healthy children aged 6 years: The COGNIS study follow-up - Diéguez, Estefanía; Nieto-Ruiz, Ana; Martín-Pérez, Cristina; Sepúlveda-Valbuena, Natalia; Herrmann, Florian; Jiménez, Jesús; De-Castellar, Roser; Catena, Andrés; García-Santos, José Antonio; Bermúdez, Mercedes G.; Campoy, Cristina (Frontiers in Nutrition, 2022)
Breastfeeding is the gold standard in infant nutrition; knowing how it influences brain connectivity would help to understand the mechanisms involved, which would help to close the nutritional gap between infant formulas and breastmilk. We analyzed potential long-term differences depending on the diet with an experimental formula (EF), compared to a standard formula (SF) or breastfeeding (BF) during the first 18 months of life on children’s hypothalamic functional connectivity assessed at 6 years old. A total of 62 children participating in the COGNIS randomized clinical trial (registered at www.ClinicalTrials.gov, Identifier NCT02094547) were included in this study. They were randomized to receive a SF (n=22) or an enriched with bioactive nutrients EF (n=20). Breastfed children were also included as control study group (BF: n=20). Brain function was evaluated using functional Magnetic Resonance Imaging (fMRI) and mean glucose levels were collected through a 24h continuous glucose monitoring (CGM) device at 6 years old. Furthermore, nutrient intake was also analyzed during the first 18 months of life and at 6 years old through three-day dietary intake records. EF and BF groups showed lower functional connectivity (FC) between the medial hypothalamus (MH) and the anterior cingulate cortex (ACC) in comparison with SF children. Moreover, BF children showed lower FC between the MH and the left putamen extending to middle insula, and higher FC between the MH and the inferior frontal gyrus (IFG) compared to the EF children group. These areas are key regions within the salience network, involved in processing salience stimuli, eating motivation and hedonic-driven desire to consume food. Indeed, current higher connectivity found on the MH-IFG network in the BF group was associated with lower simple sugars acceptable macronutrient distribution ranges (AMDR) at 6 months of age. Regarding linoleic acid intake at 12 months old, a negative association with this network (MH-IFG) only in the BF group was found. Additionally, BF children showed lower mean glucose levels compared to SF children at 6 years old. Our results may point out to a possible relationship between diet during the first 18 months of life and inclined proclivity for hedonic eating later in life.